Fecal calprotectin is not a clinically useful marker for the prediction of the early nonresponse to exclusive enteral nutrition in pediatric patients with Crohn disease - Copova, Ivana; Hradsky, Ondrej; Zarubova, Kristyna; Gonsorcikova, Lucie; Potuznikova, Kristyna; Lerchova, Tereza; Nevoral, Jiri; Bronsky, Jiri (European journal of pediatrics, 2018)
Exclusive enteral nutrition (EEN) has been recommended as the first-line therapy in children with active Crohn disease (CD). The primary aim of our study was to determine whether it is possible to use the difference between basal fecal calprotectin (F-CPT) and the value at week 2 of EEN to predict clinical response at week 6. We prospectively collected stool samples for F-CPT analysis and clinical and laboratory parameters during EEN from 38 pediatric patients (28 boys, median age 12.8 years) with newly diagnosed active luminal CD. The difference between F-CPT concentrations before EEN and at week 2 did not predict clinical non-response at week 6 (OR 0.9996 95% CI 0.9989-1.0002, p = 0.18); however, it predicted patients who did not achieve clinical remission at week 6 (OR 0.9993, 95% CI 00.9985-0.9998, p = 0.006) with sensitivity of 58%, and specificity of 92% for cut-off of F-CPT increase by 486 μg/g.Conclusions: An early decrease in F-CPT levels in children with newly diagnosed active luminal CD did not predict clinical response at week 6 of EEN induction therapy, and clinical remission was predicted with low accuracy. Therefore, F-CPT cannot be used as a predictor to select the patients in whom EEN should be terminated. What is Known: • The fecal calprotectin (F-CPT) is an important marker of intestinal inflammation. • Approximately 25% of pediatric patients with Crohn disease (CD) do not achieve clinical remission, and there is still no sufficient predictor of response to exclusive enteral nutrition (EEN) treatment. What is New: • The difference between the F-CPT concentrations before EEN treatment and at week 2 did not predict clinical response to treatment at week 6, even if it predicted clinical remission, however, with low accuracy. F-CPT is not a suitable predictor to select the patients for discontinuing of EEN induction therapy.
Keywords: Sensitivity and Specificity; senzitivita a specificita; feces; Humans; Calprotectin; dítě; Child; Response; Female; Prediction; výsledek terapie; Crohn Disease; Leukocyte L1 Antigen Complex; lidé; Biomarkers; Feces; biologické markery; ženské pohlaví; Male; Inflammatory bowel disease; Adolescent; Treatment Outcome; Remission; Crohnova nemoc; Enteral Nutrition; enterální výživa; mužské pohlaví; prospektivní studie; leukocytární L1-antigenní komplex; mladiství; Prospective Studies